Pengaruh Kemandirian, Efisiensi, Kinerja Keuangan dan Rasio Utang Terhadap Financial Sustainability pada Kabupaten/Kota di Provinsi Sumatera Selatan - Putri Meylina; Sandrayati; Anggeraini Oktarida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the influence of independence, efficiency, financial performance and debt ratio on financial sustainability in districts/cities in South Sumatra province. The data used in this study is secondary data with data obtained through the EPPID website of the Central Audit Agency of the Republic of Indonesia in 2020-2023. This type of research is a quantitative research. The sample of this study is 17 regencies/cities in South Sumatra Province. The sample determination in this study used the purposive sampling technique. The data analysis method uses multiple linear regression analysis with the help of Eviews 12 for windows. The results of this study can be concluded that partially independence and efficiency have a positive and significant effect on financial sustainability, while financial performance has a negative and significant effect on financial sustainability and debt ratio has no effect on financial sustainability. Simultaneously, the ratio of independence, efficiency, financial performance, and debt ratio has a significant effect on financial sustainability in Regencies/Cities in South Sumatra Province in 2020-2023.